Electron enriched ternary NiMoB electrocatalyst for improved overall water splitting: Better performance as compared to the Pt/C || RuO2 at high current density. (December 2022) - Mandavkar, Rutuja; Habib, Md Ahasan; Lin, Shusen; Kulkarni, Rakesh; Burse, Shalmali; Jeong, Jae-Hun; Lee, Jihoon
Highlights: Systematic investigation on the ternary Ni(MoB)2 electrocatalyst for overall water splitting. Demonstration of better performance over the standard benchmark electrodes at high current density. Demonstration of stable operation in an industrial electrochemical water splitting condition. Demonstration of comparable performances in 1 M KOH and sea water + 1 M KOH. Abstract: The high energy density and zero carbon emission makes the hydrogen energy most suitable for the next-generation alternative to reduce the greenhouse gas emissions and prevent the climate changes. In this work, the ternary nickel-molybdenum-boron (NiMoB) electrocatalyst is systematically studied and the best optimized NiMoB electrode demonstrates better electrochemical water splitting performance over the benchmark electrodes of Pt/C || RuO2 at high current density. Along with the systematic fabrication parameter optimization, the ternary NiMoB electrocatalyst with the multi-sphere morphology demonstrates significantly high active surface area, low impedance, and low reaction energy barriers with the improved crystallinity of electrodes and absorption and desorption of intermediates. The incorporation of boron in the transition metal matrix of Ni-Mo significantly boosts up the water splitting capability by lowering the kinetic barriers with the electron enriched metallic sites and improved stability of electrodes. Specifically, the turnover overpotential of 1.61 V is achieved at 50 mA/cm 2 in 1 M KOH with the improved hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) kinetics in a 2-electrode system. More importantly, the NiMoB electrocatalyst demonstrates better performances at high current range above 1250 mA/cm 2 in 1 M KOH and 1100 mA/cm 2 in seawater (SW) + 1 M KOH. The NiMoB || NiMoB also demonstrates an equivalent water splitting performance in the real SW + 1 M KOH solution. In addition, a very stable chronoamperometry (CA) operation over 12 h at 500 mA/cm 2 and 1, 000-time repetition of linear sweep voltammetry (LSV) over 8 h in 6 M KOH at 60 °C confirm that the optimized electrode can demonstrate stable and repetitive operations in an industrial electrochemical water splitting condition. Graphical abstract: Born-based spherical micro-cluster NiMoB electrode demonstrates a better water splitting performance over the benchmark electrodes of Pt/C || RuO2 at higher current in 1 M KOH. Image, graphical abstract